The Influence of Brand Image, Brand Trust, and Product Quality on Cosmetic Brand Loyalty (Study on Maybelline Lipstick Product Customers in Surabaya City Area) - Sonia Ayu Cahyani; Rusdi Hidayat Nugroho (International Journal of Economics Development Research (IJEDR), 2024)
In the era of globalization, technological advancements have begun to develop rapidly, prompting companies, especially in the skincare sector, to compete in introducing their products. Currently, the demand for cosmetics is increasing, and beauty products or cosmetics are undergoing many changes with the release of the latest innovations. Loyalty to a brand depends on the extent to which the brand image reflects its unique products, the trust it has in the brand, and the quality of products that consumers consider safe, according to their desires. The type of research used is quantitative research. The population in this study is all customers of Maybelline Lipstick products in the Surabaya City area. This study used a sample of 200 respondents using non-probability sampling method and sampling technique, namely purposive sampling. And using multiple linear regression analysis to analyze the data. The results of this study indicate that the variables of Brand Image, Brand Trust, and Product Quality collectively influence Brand Loyalty. The Brand Image variable does not have a significant impact on Brand Loyalty. The Brand Trust variable has a positive and significant effect on Brand Loyalty. The Product Quality variable also has a positive and significant effect on Brand Loyalty